Unwrapping the influence of proactive personality on job satisfaction during organizational socialization: Examining the intervening effects of person-environment fit - Soares, Sofia Martins de Pinho (2021)
Dissertação de Mestrado Integrado em Psicologia apresentada à Faculdade de Psicologia e de Ciências da Educação